Associations of maternal pre-pregnancy body mass index and gestational weight gain with risk of offspring neurodevelopment at 2 years: A Chinese birth cohort study - Dong, Xiaohan; Zhou, Aifen (Frontiers in Pediatrics, 2023)
Background： In recent decades, there has been a surge in both obesity & developmental impairments. Only a few research have looked at the relationship between gestational weight growth & pre-pregnancy BMI in mothers & the neurobehavioral development of their infants. Based on a Chinese birth cohort study, the present study examines the relationships between maternal pre-pregnancy BMI, GWG, & the risk of child neural development at 2 years of age. Methods: 3115 mother-infant pairs were registered in the Wuhan Health Baby cohort between September 2013 & October 2018, & data from this cohort was used in this investigation. The Chinese classification was used to group maternal BMI before conception. Based on the 2019 Life Cycle Project-Maternal Obesity & Childhood Outcomes Study Group, categories for GWG were created. By employing a Chinese translation of the Bayley scales for measuring infant & toddler development, the main result was an assessment of the child's neurodevelopment at age 2. (BSID-CR). Results: Infants of overweight & obese moms exhibited lower MDI scores than those of mothers with normal pre-pregnancy BMI (β＝-2.510, 95%Cl＝-4.821 to -0.200) in the entire sample. Meanwhile, we find among the normal pre-pregnancy BMI mothers, infants of inadequate GWG mothers had lower MDI scores(β＝-3.952, 95%Cl＝-7.809 to -0.094) compared with the referenced adequate GWG mothers, as well as the infants of excessive GWG mothers among the underweight pre-pregnancy BMI mothers (β＝-5.173, 95%Cl＝-9.803 to -0.543). The PDI scores of the infants were not affected by the maternal pre-pregnancy BMI & GWG. Conclusion: For Chinese babies aged 2 in this nationally representative sample, aberrant pre-pregnancy BMI and GWG can impair infants' mental development, but not psychomotor development. Such results are significant given the incidence of overweight & obesity as well as the long-term effects of early brain development. Additionally, women should be given general advice on how to achieve their ideal pre-pregnancy BMI & GWG.